Overlap in EFL Learners' Online Casual Conversation: How Men and Women Differ - Williyan, Aldha (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The COVID-19 pandemic is thought to have changed the way people communicate in society. It has ushered in a new way of living that is fully conducted online. It urges this study to concentrate on examining online communications, particularly men's and women's online casual conversations. The qualitative approach was employed to accomplish this. Three basic processes were carried out in greater depth. The first step was to tape the dialogue, which was transcribed using the theory of Eggins & Slade (1997). To strengthen the data, an unstructured interview was conducted (Mackey & Gass, 2005). Finally, to expose the phenomenon of overlap, the data were evaluated using theories proposed by numerous experts, such as Schegloff (2000), Cogo & Dewey (2012), Yule (1996), and many more. The results were afterward developed into rich verbal descriptions. Analysis shows that men's and women's online casual conversations have different patterns of overlap. This can happen because of the influence of what they have received throughout their lives about how to be a man and a woman. The gender values they get from their environment greatly affect how they communicate and interact with others.